Tourism spots detection mobile application - Wong, Wei Jun (2022)
The project is to develop a mobile application for the tourism industry in Petaling Jaya, Selangor. It will provide a guidance for the tourists to plan their self or gathering journey. It helps in assisting the tourists to the nearby tourist’s spots, restaurant, shopping mall, and transportation to go. The project designed to be a mobile application is due to the convenience of using it during the busy tourist trip. They are just required to have a smart Android mobile device to carry. The project has covered the module of detecting nearby tourist’s spots, planning your budget, scheduling your calendar, travel bucket list and forum. According to the research as shown in the Literature session, there are currently no markets for doing the tourist mobile application on the specified area of Petaling Jaya and there is only an application which is not fully developed. The application is designed and takes the ideas/ resources from various mobile applications to develop a better version of mobile application to let the user have a better experience during their trip around Petaling Jaya.